PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI KEBIJAKAN PEMBAYARAN PAJAK KENDRAAN BERMOTOR DI KOTA JAYAPURA - Gideon Thomas A.P Fatem; Agustinus Fatem (JURNAL KEBIJAKAN PUBLIK, 2021)
This article aims to analyze public participation in the payment of motor vehicle taxes in the city of Jayapura. Then the supporting and inhibiting factors in community participation in the implementation of motor vehicle tax payment policies in the city of Jayapura. As well as analyzing the efforts made in increasing community participation in the implementation of PKB policies in the city of Jayapura. The research method is descriptive research using a qualitative approach. The phenomenon observed in this research is how the implementation of Regional Regulation No. 7 of 2016 in increasing public participation in the implementation of motor vehicle tax payment policies in the city of Jayapura. The results showed that . All officers and employees follow the rules or legal basis of the police and their main duties and functions (duties, principals and functions) according to applicable regulations. However, in collecting motor vehicle taxes there are problems, but all of them must be normally resolved by the UPPD Samsat Kota Jayapura office. Supporting factors include supporting factors internally and externally from the support of the community and other relevant stakeholders. while the inhibiting factors are the level of compliance of the policy target groups, both supporting resources and HR personnel owned. Then, the efforts that need to be done are Optimizing socialization, Optimizing advertising / promotions, Maximizing services, Revitalizing traffic orderly areas, Conducting raids, Increasing infrastructure support, and Providing officer allowances.